Analisis dan Perancangan Sistem Informasi Persediaan Barang Toko Lingga Dengan Metode Waterfall - Windy; Liu, Evelyn (Fakultas Komputer - Universitas Universal, 2021)
Toko Lingga is one of the local stores based in Batam City that focuses on selling building materials needs fast and easy information systems to fulfill the operational needs. At this moment, Toko Lingga still doesn't have a convenient way of recording and collecting data in the inventory system. To know the available stocks, the administration needs to go to the warehouse to check the available stocks one by one. Because of that, information that needs to be shared with other parties is hard to give and not accurate. To support this research, researchers use a Software Development Lifecycle (SDLC) with the waterfall method, also with ERD and UML. With this information system based on the android app, Toko Lingga will have a better way to collect information in a short moment and accurate data.